TAP polymorphism does not influence transport of peptide variants in mice and humans - Obst, Reinhard; Armandola, Elena A.; Nijenhuis, Marga; Momburg, Frank; Hämmerling, Günter J. (European journal of immunology, 1995)
The major histocompatibility complex (MHC)-encoded transporter associated with antigen processing (TAP) delivers cytosolic peptides to the lumen of the endoplasmic reticulum (ER) for presentation by MHC class I molecules. For the rat, it has been demonstrated that TAP polymorphism results in the selection of different sets of peptides, the nature of the C terminus being of particular importance. Here, we investigated whether TAP polymorphism in mice and humans has functional consequences for transport of peptide sets variable at the C-terminal residues. Using cell lines of H-2d, H-2k, and H-2dxk haplotype and a panel of human lymphoblastoid cell lines expressing eight different TAP alleles, we detected species-specific transport patterns, but no significant influence of TAP polymorphism on peptide selection. In addition, peptides with different core sequences were translocated to the same extent by different TAP. These results suggest that a major contribution of human TAP polymorphism to disease progression and autoimmunity is not very likely.